ANALISIS PENGARUH RASIO KEUNGAN DAN PERTUMBUHAN ASET TERHADAP DIVIDEN PERSHARE INDUSTRI WHOLE SALE AND RETAIL TRADE - Tona Aurora Lubis; Agus Syarif; Mulia Inda Purwati (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The purpose of this research is to examine the effect of Current ratio, Cash ratio, Debt to Total Equity (DER), Return on Investment (ROI), Earning per Share (EPS), Asset GrowthÂ toward Dividend per Share (DPS) in industry Wholesale and Retail Trade that is listed in BEI at the periode of 2009-2012. Sampling technique used is purposive sampling that fulfied these criterion (1) the company that trade their stocks in Bursa Efek Indonesia (BEI); (2) the company that represents their financial report per December 2009-2012; and (3) the company that continually share their dividend per December 2009-2012. According to those criteria, it is found sample size as many as 15 companies from 22listed companies.Reserach results show that simulteneusly, all examined variable effect DPS significantly. Otherwhile, partially the variables that effect DPS significantly are EPS and Asset Growth, but CR, DER, ROI not significant. Furthermore cooefficent determintasion (R) is 68,9 percent that implies that 31,10 percent is not explained by the variable examined in this research.Keywords: Current ratio, Cash ratio, DER, ROI, EPS, Deviden Policy and Indonesian Capital Market